Comparison of Enterococcus Species Diversity in Marine Water and Wastewater Using Enterolert and EPA Method 1600. (10th June 2013) - Ferguson, Donna M.; Griffith, John F.; McGee, Charles D.; Weisberg, Stephen B.; Hagedorn, Charles
Abstract : EPA Method 1600 and Enterolert are used interchangeably to measure Enterococcus for fecal contamination of public beaches, but the methods occasionally produce different results. Here we assess whether these differences are attributable to the selectivity for certain species within the Enterococcus group. Both methods were used to obtain 1279 isolates from 17 environmental samples, including influent and effluent of four wastewater treatment plants, ambient marine water from seven different beaches, and freshwater urban runoff from two stream systems. The isolates were identified to species level. Detection of non- Enterococcus species was slightly higher using Enterolert (8.4%) than for EPA Method 1600 (5.1%). E. faecalis and E. faecium, commonly associated with human fecal waste, were predominant in wastewater; however, Enterolert had greater selectivity for E. faecalis, which was also shown using a laboratory-created sample. The same species selectivity was not observed for most beach water and urban runoff samples. These samples had relatively higher proportions of plant associated species, E. casseliflavus (18.5%) and E. mundtii (5.7%), compared to wastewater, suggesting environmental inputs to beaches and runoff. The potential for species selectivity among water testing methods should be considered when assessing the sanitary quality of beaches so that public health warnings are based on indicators representative of fecal sources.